2022
DOI: 10.1021/acsami.2c11200
|View full text |Cite
|
Sign up to set email alerts
|

Oncocyte Membrane-Camouflaged Multi-Stimuli-Responsive Nanohybrids for Synergistic Amplification of Tumor Oxidative Stresses and Photothermal Enhanced Cancer Therapy

Abstract: The combination of various therapeutic modalities has received considerable attention for improving antitumor performance. Herein, an innovative nanohybrid, namely CaO 2 @FePt-DOX@PDA@CM (CFDPM), was developed for synergistic chemotherapy/chemodynamic therapy/Ca 2+ overloading-mediated amplification of tumor oxidative stress and photothermal enhanced cancer therapy. Camouflage of the 4T1 cell membrane enabled CFDPM to escape the immune surveillance and accumulate in the tumor tissue. Ca 2+ , released from CaO … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 53 publications
(75 reference statements)
0
12
0
Order By: Relevance
“…[66] Although CaO 2 does not play a direct role in promoting PTT treatment, it can indirectly alleviate the hypoxic microenvironment of tumors, and the Ca 2+ generated can amplify the oxidative stress of tumor cells. Hence, CaO 2 serves mainly as a drug carrier material in PTT, offering [67] Copyright 2022, American Chemical Society.…”
Section: Pttmentioning
confidence: 99%
See 1 more Smart Citation
“…[66] Although CaO 2 does not play a direct role in promoting PTT treatment, it can indirectly alleviate the hypoxic microenvironment of tumors, and the Ca 2+ generated can amplify the oxidative stress of tumor cells. Hence, CaO 2 serves mainly as a drug carrier material in PTT, offering [67] Copyright 2022, American Chemical Society.…”
Section: Pttmentioning
confidence: 99%
“…Figure 8. a) The preparation path of CFDPM NPs; b) the therapeutic principles of synergistic therapy in tumor cells; c) the fluorescent images of living cells; d) the fluorescence intensity analysis of major organs and tumor cells and tissues after treatment for 12 h; e) the tumor tissue cells are stained with different staining agents; f) the photothermal images. Reproduced with permission [67]. Copyright 2022, American Chemical Society.…”
mentioning
confidence: 99%
“…Besides, CaO 2 could also be utilized as a drug carrier for loading drugs that destroy cellular Ca 2+ buffering capacity, promote Ca 2+ influx, or inhibit Ca 2+ efflux, thereby enhancing the Ca 2+ overload efficiency. [56,57] For instance, it was found that the Transient Receptor Vanilloid 1 (TRPV1) thermosensitive cation channel could promote Ca 2+ influx when the temperature exceeds 43 • C. Based on this finding, Zhou and colleagues designed a near-infrared (NIR)-responsive DPPC-DSPE-PEG2000-NH 2 @PDPP@CaO 2 @doxorubicin NPs to acquire chemotherapy, Ca 2+ overload and PTT. [58] With NIR irradiation, the PTT effect could elevate the local temperature at the tumour site, activating the TRPV1 channel and promoting Ca 2+ influx to achieve more efficient Ca 2+ overload therapy.…”
Section: Cao mentioning
confidence: 99%
“…The combined FePt could convert H 2 O 2 produced by CaO 2 into HO•, leading to enhanced apoptosis. [85] In another work, CaO 2 nanomaterials modified by Fe 3+ /TA (tannic acid) polyphenol network were prepared to treat cancer by Ca 2+ overload and CDT. [86,87] Notably, HO• generated via the Fenton reaction desensitized the intracellular calcium ion proteins, promoting the occurrence of calcium overload and accelerating the death of cancer cells.…”
Section: Cao 2 -Based Nanomaterialsmentioning
confidence: 99%